Choice editing for sustainable development : consumer attitudes toward food retailers limiting food choices - Biro, Andrea; Svensson, Emma (SLU/Department of Molecular Sciences, 2021)
Society is facing significant challenges in transforming to a sustainable food system where healthy food is provided, while reducing the negative environmental impact. Yet, it is debatable whose responsibility it is to provide healthy, environmentally friendly food from sustainable food systems. As food retailers have huge power through their supply and placement, it has been argued that they could steer consumers towards sustainable choices. Shifting from nudging- and sustainability marketing initiatives towards retail led in-store choice restrictions have therefore been suggested to enable a sustainable food system but has not been executed to great extent due to the fear of losing consumers. The aim of the study was to explore consumer understandings of and attitudes towards retail led in-store choice restrictions aiming to reduce the negative environmental and health impacts from food consumption. This was assumed to provide insights regarding where the perceived burden of responsibility lies and in what ways food retailers could be a leverage point for shaping sustainable consumption. The study used a qualitative approach where four semi-structured individual interviews with Axfood, Coop, ICA and WWF as well as four semi-structured focus group interviews with consumers were conducted and continuously integrated with a literature review. A content analysis of the collected empirical data was conducted with the help of the theoretical framework following Kahneman’s fast- and slow thinking systems, perceptions, the Functional Theory of Attitudes, nudging, choice editing and different types of paternalism. The results indicated that consumers have diverse attitudes towards paternalistic measures. Food retailers' choice editing strategies aiming to reduce the negative environmental impacts from food consumption were highly encouraged and accepted due to a perceived collectivistic responsibility for maintaining our common earth. On the other hand, food retailers’ choice restrictions aiming to reduce the negative health impacts met great disapprovals, due to health limitations being perceived as an insult towards consumers' individual body, identity and liberty. However, eliminations contributing to a greater overall health- and well-being was encouraged only if executed by legitimate and trusted authorities with reasonable, non-profitable driving forces where a democratic society was at the foundation. Choice editing is not an easy strategy for food retailers to apply as it interferes with consumers freedom of choice but is necessary as nudging and sustainability marketing are too soft strategies to steer consumer's often irrational decision-making and will not be enough for a global, sustainable transition. However, food retailers alone cannot bear the responsibility- or be the only leverage point as governmental measures are needed.